التطور التاريخي لقانون الجمنا ستك الفني للرجال منذ عام 1949م ولغاية عام 2017 م: Historical Development of Men Artistic Gymnastics Code Since 1949 Until 2017 - Majeed, Saleh; Sakran, Jamal (Journal of Physical Education, 2018)
To study the history of any subject opens the window of the past to appreciate the development. The importance of the research lies in scanning the history of gymnastics specially men’s artistic gymnastics by using men Artistic gymnastics code (1949) as the main reference. This code is the most important event that changed gymnastics. In 1949 the first issue of the International Federation men Artistic gymnastics code was published. The researchers studied the changes in men Artistic gymnastics code. The results of the study showed that the first international men Artistic gymnastics code in 1949, after which it was updated every four years to suit the development of its equipment, the degree the gymnastic player gets for artistic performance; from ten degrees to an open degree, a matter that led to great development in gymnastics’ motor skills.